Psikolojik belirtiler ve dürtüsellik ile problemli sosyal medya kullanımı arasındaki ilişki - Tutal, Ömer; Erensoy, Habib; Luş, Melek Gözde (Journal of Dependence, 2021)
Objective: In this pilot study, the relationship between problematic social media use, impulsivity, and psychological symptoms in adults was investigated. Method: In this study conducted with 178 people, demographic information form, Social Media Addiction Scale, Barratt Impulsiveness Scale and Brief Symptom Inventory were applied to the participants. Results: Social media addiction levels of the participants were found to be significantly higher in women, singles, graduate graduates, those who spend more than 8 hours in social media, and Twitter and Instagram users. When the relationship between problematic social media use, impulsivity, and psychological symptoms was examined, virtual tolerance and virtual communication sub-dimensions of social media addiction were positively and significantly related to all sub-dimensions of impulsivity and psychological symptoms. In addition, the increase in the social media addiction scores of the participants was significantly predicted by the dimensions of unplanned impulsivity, depression, anxiety and somatization. Conclusion: There are significant psychological factors that may be associated with the problematic use of social media, which has become an important part of the daily life of adults.